A potential cost savings analysis of a penicillin de-labeling program - Dong, Yilu; Zembles, Tracy N.; Nimmer, Mark; Brousseau, David C.; Vyles, David (Frontiers in Allergy, 2023)
Introduction: Over 95% of patients documented as penicillin allergic can tolerate a penicillin without a reaction. Inaccurate documentation of penicillin allergy leads to more expensive alternative antibiotic prescriptions and an increased incidence of resistant infections. Objective: To understand the potential drug cost savings of a penicillin de-labeling program to a healthcare system. Methods: We evaluated patient visits with documented penicillin allergy who presented to the pediatric Emergency Department (PED) and 22 associated primary care clinics. Patients were included if they were discharged home with a non-penicillin antibiotic when the first-line treatment for the diagnosis would have been a penicillin. The potential cost savings were the sum of all visit-level cost differences between the non-penicillin prescription(s) and a counterfactual penicillin prescription. To factor in a 95% successful patient de-labeling rate, we repeatedly sampled 95% from the patients with the eligible visits 10,000 times to produce an estimate of the potential cost savings. Results: Over the 8-year period, 2,034 visits by 1,537 patients to the PED and 12, 349 visits by 6,073 patients to primary care clinics satisfied eligibility criteria. If 95% of the patients could have been successfully de-labeled, it would have generated a cost saving of $618,653 (95% CI $618,617 – $618,689) for all the corresponding payers in the system. Conclusions: Implementing a penicillin de-labeling program across a healthcare system PED and its associated primary care clinics would bring significant cost savings. Healthcare systems should rigorously evaluate optimal methods to de-label patients with reported penicillin allergy.